Ascending aortic coarctation-an atypical location in a non-takayasu arteritis female patient - Öteyaka, Emre; Kuğuoğlu, Okan Eren; Sarı, Gizem; Basunlu, Mehmet Turan; Doğan, Mehmet Sait; Çalış, Elif; Hakgör, Aykun; Türkoğlu, Halil; Uğurlucan, Murat (Sociedade Brasileira de Cirurgia Cardiovascular, 2023)
Coarctation of the aorta is a well-known congenital cardiovascular disorder that typically occurs within proximity to the ductus arteriosus. The ascending aorta, distal descending aorta, and abdominal aorta are segments which are prone to development of an atypical coarctation. The etiologies of atypical cases are usually associated with various types of vasculitis syndromes or underlying genetic disorders. In this report, we present a 24-year-old female patient with an ascending aortic coarctation which developed secondary to an atherosclerotic process.
Keywords: Aortic Coarctation; Atherosclerosis; Takayasu Arteritis